Core-crosslinked micelles with a poly-anionic poly(styrene sulfonate)-based outer shell made by RAFT polymerization. (14th March 2022) - Wang, Hui; Fliedel, Christophe; Manoury, Eric; Poli, Rinaldo
Abstract: Core-crosslinked micelles (CCMs) with a permanently charged anionic shell of sodium poly(styrene sulfonate) (PSS – Na + ) chains have been developed by a convergent three-step one-pot RAFT polymerization starting with 4-cyano-4-thiothiopropylsulfanyl pentanoic acid (CTPPA, R0 -SC(S)S n Pr) as chain transfer agent, which includes polymerization-induced self-assembly (PISA) in the second step. The final crosslinking step of the R0 -(SS - Na + ) x - b -St y -SC(S)S n Pr diblock chains was carried out with diethylene glycol dimethacrylate (DEGDMA), either diluted into styrene (DEGDMA/St = 10:90) or neat. The morphology of the intermediate micelles and of the final CCM particles was studied by dynamic light scattering (DLS) and transmission electron microscopy (TEM) as a function of the relative degrees of polymerizations for the shell, core, and crosslinking blocks. Conformational instability was observed for the aqueous dispersions of the diblock micelles, especially with the shorter PSt blocks, yielding equilibria with single chains and large agglomerates. However, crosslinking led to well-defined CCMs with narrow size distributions for the optimized polymer compositions. The DLS analysis in a compatibilizing 60:40 THF/H2 O solvent mixture demonstrates that the final step of the polymer synthesis has quantitatively crosslinked all diblock arms. Graphical abstract: Image 1 Highlights: Latexes of amhiphilic star polymers with a polystyrene sulfonate shell have been prepared by polymerization-induced self-assembly. Delicate equilibria are established between single chains, micelles and larger agglomerates. The shell-shell Coulombic repulsion blocks the particle interpenetration and avoids macrogelation during crosslinking.